Pemberian Pemahaman dan Cara Menghindari Malpraktik Bidang Profesi Kesehatan bagi Mahasiswa STIKES Pasapua Ambon - Dwight Nusawakan; Abdul Malik Mufty; Nurul Chaerani Nur; Harianti Fajar; Yosef Marsianus Karno (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2026)
Malpractice in the health professions is one of the issues that can cause harm to patients, health professionals, and healthcare institutions. A lack of understanding among students as prospective health professionals regarding ethical aspects, legal principles, professional standards, and proper service procedures may increase the risk of malpractice. This Community Service activity aims to provide students of STIKES Pasapua Ambon with an understanding of the concept of malpractice, the factors causing malpractice, and preventive efforts through the implementation of professional ethics, compliance with standard operating procedures, effective communication, and the improvement of professional competence. The activity was carried out through counseling, educational sessions, interactive discussions, and guidance on health law for participants. The results of the activity indicate an increase in students’ knowledge and awareness of the importance of understanding the limits of professional authority, legal responsibility, and preventive measures to avoid malpractice in healthcare practice. This activity is expected to help develop future health professionals who are professional, ethical, and responsible in providing safe and high-quality healthcare services.